KARAKTER TOKOH UTAMA DALAM NOVEL KUBAH KARYA AHMAD TOHARI: KAJIAN PSIKOLOGI SASTRA - Amri, Amri; Effendy, Chairil; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ This research is motivated by the desire to find the main character in the novel Kubah Karya Ahmad Tohari. A common problem in this research is